DCD and ADHD: A genetic study of their shared aetiology - Martin, Neilson; Piek, Jan; Hay, David (Elsevier BV; North Holland, 2006)
Previous studies have found that rates of attention deficit hyperactivity disorder (ADHD) and developmental coordination disorder (DCD) are very similar, both being approximately 7% in sample populations [Kadesjö, B., & Gillberg, C. (1999). Developmental coordination disorder in Swedish 7-year-old children. Journal of the American Academy of Child and Adolescent Psychiatry, 38, 820–828; Milberger, S., Faraone, S., Biederman, J., Testa, M., & Tsuang, M. (1996). New phenotype definition of attention deficit hyperactivity disorder in relatives for genetic analyses. American Journal of Medical Genetics, 67, 369–377]. The rate of comorbidity between the two has been found to be close to 50% [Barkley, R. (1990). Attention deficit hyperactivity disorder: A handbook for diagnosis and treatment. New York: Guilford Press]. Investigations into the comorbidity of the disorders points to a shared aetiology between them. The aim of the present investigation was to examine the extent to which the shared aetiology is due to common genetic factors to both disorders. We also investigated whether particular subtypes of each disorder were more linked than others. Mailed questionnaires were completed by parents (predominantly mothers) of 1285 twin pairs aged 5 and 16 years from the volunteer Australian Twin Registry (ATR). Included were a DSM-IV-based ADHD form, the alternative SWAN (Strengths and Weaknesses of ADHD Symptoms and Normal Behaviour scale) and the Developmental Coordination Disorder Questionnaire (DCDQ). Statistical analyses including structural equation modelling were carried out to explore the genetic factors of both disorders. The modelling showed a strong shared additive genetic component between most subtypes of ADHD and DCD to the subtypes of the other disorder. Analyses comparing the two ADHD measures showed an overlap of the symptoms captured by each measure but also significant differences. The DCD-fine motor and ADHD-Inattentive were most strongly linked using the DSM-IV based scale. On the SWAN scale the results were similar but the general coordination scale was also very strongly linked. Implications for the use of different assessment tools are discussed.